Population-level impact of adverse early life conditions on adult healthy life expectancy in low- and middle-income countries. (2nd January 2022) - Beltrán-Sánchez, Hiram; Palloni, Alberto; Huangfu, Yiyue; McEniry, Mary
Abstract : Evidence from theories of Developmental Origins of Health and Disease (DOHaD) suggests that experiencing adverse early life conditions subsequently leads to detrimental adult health outcomes. The bulk of empirical DOHaD literature does not consider the nature and magnitude of the impact of adverse early life conditions at the population level. In particular, it ignores the distortion of age and cohort patterns of adult health and mortality and the increased load of chronic illness and disability that ensues. In this paper, we use a microsimulation model combined with empirical estimates of incidence and prevalence of obesity, type 2 diabetes, and associated disability in low- and middle-income countries to assess the magnitude of delayed effects on adult healthy life expectancy and on compression (or expansion) of morbidity at older ages. The main goal is to determine if, in what ways, and to what extent delayed effects due to early conditions can influence cohorts' chronic illness and disability profiles.